Dynamic Mechanical Properties and Thermal Stability of Poly(lactic Acid) and Poly(butylene Succinate) Blends Composites (Journal of Fiber Bioengineering and Informatics, 2013)
The blend of poly(lactic acid) (PLA) and poly(butylene succinate) (PBS) were prepared and extrudedwith various compositions and their molded properties were examined. Thermogravimetric analysisshowed that thermal stability of the blends was higher than that of pure PLA and the weight loss ofPLA/PBS (40/60 wt%) was lower than neat polymers. Differential scanning calorimetry thermogramsof blends indicated that the thermal properties of PLA did not change noticeably when blended withPBS. The tensile strength and modulus of blends decreased with the increasing PBS content. Butimpact strength has improved about two times compared to pure PLA. Rheological results revealed thatthe addition of 10% and 20% of PBS increased the storage modulus, loss modulus and viscosity of theblend at nearly all frequencies, and decreased viscosity with increasing shear stress. Dynamic mechanicalproperties results showed the lowering of storage modulus of all blended PLA which indicated the increaseof molecular mobility by adding PBS due to lower glass transition.